Solve for y 6y+9-4y=-3

Math
6y+9-4y=-3
Subtract 4y from 6y.
2y+9=-3
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 9 from both sides of the equation.
2y=-3-9
Subtract 9 from -3.
2y=-12
2y=-12
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2y=-12 by 2.
2y2=-122
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2y2=-122
Divide y by 1.
y=-122
y=-122
Divide -12 by 2.
y=-6
y=-6
Solve for y 6y+9-4y=-3

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top